2022
DOI: 10.4103/jehp.jehp_1037_21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the status of occupational health management and job satisfaction among farmers

Abstract: BACKGROUND: Job satisfaction is one of the most important issues related to human resources in the organization which can reduce organizational productivity. In this regard, occupational health is an important science related to the health of the workforce in any organization, paying attention to it will help health promotion. The aim of the present study was to determine the relationship between the status of occupational health management and job satisfaction among farmers with a health promotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…According to the WHO statistics, Safarian et al said musculoskeletal disorders are the second most common work-related disease ( 24 ). According to Anagha, one of the most important causes of musculoskeletal disorders among workers is awkward posture ( 25 ). Recent statements can confirm the results provided by our proposed model.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO statistics, Safarian et al said musculoskeletal disorders are the second most common work-related disease ( 24 ). According to Anagha, one of the most important causes of musculoskeletal disorders among workers is awkward posture ( 25 ). Recent statements can confirm the results provided by our proposed model.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of preventive programs should also be reflected in the improvement of the level of quality of life of employees [74,75]. In case of a decrease in occupational safety control, there was an increase in trauma and an incidence that may lead to a decrease in the level of quality of life of healthcare practitioners [76][77][78][79][80][81]. A number of authors have found that exposure of medical personnel to EMR may be associated with adverse effects on their cardiovascular system [82].…”
Section: Life Quality Level As An Indicator Of the State Of Healthmentioning
confidence: 99%
“…Cuantitativo La intervención psicológica en el entorno del empleado beneficia su estancia en el trabajo. Shiri et al (30) (2023)…”
Section: Cuantitavounclassified
“…La intervención en Psicología de la Seguridad ha dado resultados satisfactorios, pues han ayudado a que los accidentes disminuyan y se incremente la seguridad laboral. (47) Shiri et al (30) , introduce la necesidad de intervenciones cocreativas, que se trata de una operación procedimental que evalúan las perspectivas de los empleados a fin de realizar medidas a largo plazo; no obstante, resaltan que la conjunción entre baja remuneración y la excesiva exigencia laboral afecta negativamente la estabilidad mental de los empleados.…”
Section: Intervención Psicológicaunclassified